Digitalization of the technological process of oil treatment; Химия и химическая технология в XXI веке; Т. 2 - Chernyshov V. N. Viktor Nikolaevich; Dolgov I. R.; Zebzeev A. G.; Belinskaya N. S. Natalia Sergeevna (2025, 2025)
Заглавие с экрана